Comparisons of 3D- and 2D-measurement techniques and observational real-time assessment of frontal plane knee control in a vertical drop jump landing - Steffen, K.; Kroken, T.; Krosshaug, T. (British Journal of Sports Medicine, 2014)
Background: Poor frontal plane knee control is suggested to be a risk factor for anterior cruciate ligament injuries. Both 3D motion analysis and less complex methods, such as 2D video analysis and subjective assessments, have been used to assess frontal plane knee motion. However, the agreement between all three methods has not been investigated. Objective: To determine the agreement between 3D and 2D motion analysis and real-time observational assessment of frontal plane knee control in a vertical drop jump (VDJ) landing. Design: Observational study.Setting Research laboratory.Participants 119 Norwegian female elite handball players.Risk factor assessment Players performed a VDJ during which movement was recorded with a 3D motion analysis system, a digital video camera, and real-time observational screening in frontal plane. Main outcome measurements: 3D and 2D knee-to-ankle separation ratios were calculated to assess frontal plane knee control. A physiotherapist independently scored the knee control as "good", "reduced" or "poor". All variables were assessed at peak knee flexion. Results: Correlations between 3D and 2D knee-to-ankle-separation ratios and 2D and 3D versus real-time observation ranged from 0.63 to 0.75. Mean 3D and 2D knee-to-ankle-separation ratios were significantly lower for players being scored with "poor" compared to those with "reduced" or "good" frontal knee control. Conclusion: Compared with the "gold standard" (3D analysis), both 2D motion analysis and real-time observations seem to be feasible tests to assess frontal knee control. The injury predictive value of the VDJ screening test remains to be answered.